Pathogenesis of Feline Panleukopenia Virus in Susceptible Newborn Kittens I. Clinical Signs, Hematology, Serology, and Virology - Csiza, C. K. (1971)
Inoculation of susceptible newborn kittens with a large dose of panleukopenia virus caused subclinical infection in 19 of 23 cases. All infected kittens developed severe and prolonged leukopenia. Cell-free virus was present in the blood from 1 to 7 postinoculation days. The virus spread to all organs, regardless of the route of inoculation. The thymus, spleen, mesenteric lymph nodes, and the cerebellum were the most severely infected organs. Kittens responded to virus infection by production of specific antibodies, first detectable in the circulatory system 6 to 8 days after infection. Antibody production preceded recovery from leukopenia by 3 days.